Efecto de la harina de tagetes erecta en la canal y la pigmentación de la piel del pollo broiler - Elizalde Gallardo, Maria Fernanda (2017)
This research was conducted in the Santa Inés farm of the Academic Unit of Agricultural Sciences of the Technical University of Machala Province of El Oro, whose objective was to evaluate the effect of T. erecta flower flour in the productive parameters, Skin and chicken meat. The results obtained were the productof work of a 35 days with 200 Cobb 500 chickens, handled according to the standards of poultry production, these were distributed in five groups: Treatment 1 (control), treatment 2 (T. erecta 0.05%), Treatment 3 (T. erecta 0.10%), Treatment 4 (T. erecta 0.15%) and Treatment 5 (T. erecta 0.20%), each with four repetitions, where 10 chickens were placed on random.To carry out this research, we used antibiotic-free promoter growth, artificial pigmentation-free poultry feed, which was acquired in "BALMAR", a poultry feed plant located in the Cantón Balsas Province of El Oro. Food consumption data were recorded weekly, daily water consumption, weekly poultry weight and tarsus colorimetry weekly. The variables to be investigated were: live animal weight (g), comsupmtion of food (g), water consumption (g), feed conversion, mortality, organoleptic indicators (chicken meat weight and sensorial analysis), colorimetry and abdominal fat thickness. To generate the data of organoleptic indicators, 40 chickens were taken at random, 2 of each replica, (male and female), which were slaughtered and data were obtained; Live weight, tarsus colorimetry, bleeding weight, weight without feathers, weight without viscera, weight without neck and legs, breast weight, frozen breast weight and abdominal fat thickness. For this purpose, a (CAMRY Brand) scale was used with a margin of error of 1g, and the fat thickness data were obtained using a digital caliper 0-150 mm (TACTIX Brand). In the determination of the test consumer tasting, 100 g of each breast were cooked for 20 minutes, after this was measured the lost of juices of each simple and then perform the respective test in the Academic Unit of Sciences. To be repeated with an interval day, in which participed teachers, students and administrative staff. Among the results obtained in our research we found significant statistical differences when comparing them with the absolute control in terms of food consumption, coloration, abdominal fat thickness, juice loss, the best results were obtained with the inclusion of flour of T. erecta flower at 0.15% and 0.20%. with respect to food conversión and wáter consumption, we did not have significant values. No mortality was recorded throughout the experiment. The organoleptic indicators showed a greater acceptance in treatments T4 (0.15%) and T5 (0.20%), not finding a negative difference in the control. We can conclude that the inclusion of T. erecta flour was effective in terms of coloration and organoleptic qualities of the chicken meat.